Strategi Visual dan Estetika Konten dalam Peningkatan Awareness terhadap Batik Lampung di Instagram - Carolina, Thabita; Purnamasari, Melan Susanty (Business Perspective Journal, 2025)
The promotion of traditional batik through social media has become a vital strategy for enhancing brand awareness and preserving local cultural heritage. This study aims to analyze the visual and aesthetic strategies used to promote Lampung Batik on Instagram, focusing on three primary accounts: @batiksiger, @deandrabatiklampung, and @batik_gabovira. The research addresses the issue of inconsistent and suboptimal use of visual elements in enhancing brand awareness and audience engagement on social media. This study employed a qualitative content analysis method with a descriptive approach. Data were collected through direct observation of visual content, including photos, videos, color schemes, and aesthetic compositions. The study also examined the use of interactive features and audience responses to each type of content to assess the effectiveness of promotional strategies. The findings reveal that vibrant colors, cultural backgrounds, and consistent storytelling are the most effective visual elements for increasing awareness of Lampung Batik. The three Instagram accounts utilized these elements with varying levels of success, with @batiksiger and @deandrabatiklampung demonstrating greater visual consistency and audience engagement. However, improvements can be made in using advanced Instagram features such as IG Live and cross-account collaborations to further enhance promotional efforts. The study concludes that well-structured visual elements and compelling cultural storytelling significantly improve the effectiveness of Lampung Batik promotion on Instagram. It is recommended that batik UMKM adopt these insights to develop more diverse and interactive content strategies to strengthen audience engagement and cultural identity. Future research could explore the use of narrative video formats and conduct regular evaluations to assess the effectiveness of different visual promotional strategies. Keywords: visual strategy, promotion, brand awareness, visual aesthetics, Batik Lampung